PELATIHAN TEKNIS KEPARIWISATAAN DI DESA WISATA SUNGAI LANGKA DAN WIYONO - Eksa Ridwansyah; Enggar Dwi Cahyo; Damara Saputra Siregar; Meyliana Astriyantika; Anwar Rahman; Refdi Akmal (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Looking at the potential for the development of the Wiyono and Sungai Langka tourist villages, the objectives of this activity are: 1) to train the community in compiling and packaging tourism package products; 2) train professional tour guides; 3) train homestay management. Methods The implementation of the activity is a participatory approach with lecture, discussion and direct practice methods. The result of this activity is an increase in the knowledge and ability of the community in the development of tourist villages. This increase is seen from the product components that have been identified to be included in the tour packages to be marketed, the list of names of people who are ready to become tour guides and ready to be certified for competence, as well as the existence of residents' homes that are ready to be managed into homestays as places for tourists to live. visit